2020
DOI: 10.1002/cncy.22382
|View full text |Cite
|
Sign up to set email alerts
|

Putting morphology to the test: An established classification scheme reliably stratifies salivary gland cytology by risk of malignancy with substantial interobserver agreement

Abstract: Background The Milan System for Reporting Salivary Gland Cytopathology describes several salivary gland fine‐needle aspiration cytology (SGFNAC) morphologies developed by Griffith et al. Basaloid neoplasms are pleomorphic (PB) or monomorphic with fibrillary (MBFib), hyaline (MBHy), or other (MBOther) matrix. Oncocytoid neoplasms can be pleomorphic (PO), demonstrate granular and/or vacuolated cytoplasm (OGV), or be monomorphic with mucinous (MOMuc), cystic (MOCyst), or other (MOOther) background. In the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…Interobserver agreement for categorization of samples of a basaloid morphology with varying amounts of stroma is fair with a Fleiss' κ varying from 0.11 to 0.59 depending on nuclear morphology, type of stroma and study reporting the results. 22 Approximately 20% of cases with a basaloid morphology are placed in the SUMP category but interobserver agreement for this category is only fair with a Cohen's κ of 0.28 in our study and a reported Fleiss' κ of 0.024. 23 These findings suggest that while the SUMP category may be clinically useful, it is a category with only fair to poor reproducibility and ability to predict the type of neoplasm present or the benign or malignant behavior of neoplasms with a basaloid morphology and variable amounts of stroma.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Interobserver agreement for categorization of samples of a basaloid morphology with varying amounts of stroma is fair with a Fleiss' κ varying from 0.11 to 0.59 depending on nuclear morphology, type of stroma and study reporting the results. 22 Approximately 20% of cases with a basaloid morphology are placed in the SUMP category but interobserver agreement for this category is only fair with a Cohen's κ of 0.28 in our study and a reported Fleiss' κ of 0.024. 23 These findings suggest that while the SUMP category may be clinically useful, it is a category with only fair to poor reproducibility and ability to predict the type of neoplasm present or the benign or malignant behavior of neoplasms with a basaloid morphology and variable amounts of stroma.…”
Section: Discussioncontrasting
confidence: 55%
“…19 That study demonstrated a Fleiss' κ for overall categorization agreement of 0.69. 22 We thought that interobserver agreement might be poorer for the diagnostically difficult category of basaloid neoplasms. This hypothesis is supported by the study of Lubin, et al 22 where 33 cases classified as basaloid neoplasms with variable types of stroma disclosed Fleiss' κs varying from 0.59 to 0.11.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, the pleomorphic tumors (basaloid or oncocytic) were excluded from the SUMP category because of their almost 100% association with ROM 5,6 . Subsequently, there have been several studies that have reported the risk of neoplasm (RON) and ROM for SUMP as a category in its entirety, 2,3 but only a limited number of studies have focused primarily on determining the RON and ROM for the SUMP subcategories 7‐11 . This study was aimed at evaluating the RON and ROM for the basaloid and oncocytic subtypes of the SUMP category for primary salivary gland neoplasms.…”
Section: Introductionmentioning
confidence: 99%